Manajemen Pembesaran Kerapu Tikus (Cromileptes altivelis) di Balai Besar Pengembangan Budidaya Air Payau (Bbpbap) Jepara Jawa Tengah [Nursery Management Of Grouper (Cromileptes altivelis) In Development Brackish Water Center Jepara Center Java] - Wahyu Tjahjaningsih; Atmirah Septinawati (Jurnal Ilmiah Perikanan dan Kelautan, 2010)
AbstractThe mouse grouper is variance of grouper that have high economic value because it have high sale value so that it will increase income of aquaculturist. The right management of grouper nursery would increase production to supplied the marketing demand. The aims of this case study were to know how nursery management of grouper and factors that influence in grouper nursery in BBPBAP Jepara, was held on 28 July until 28 August 2005. Method used were descriptive method with collection of primary data and secondary data. Data was taken by observation, interview, active participation and literature study. Nursery of grouper fish carried out by BBPBAP Jepara under Departement of Marine and Fisheries. Source of fry were obtain from hatchery division in BBPBAP. Marine water were obtain from the sea, while fresh water were obtain from well. Fish feeding were use trash fish which were cut to suitable with mouth gapes of fish as much 90 gram, twice a day were morning and afternoon. In the fish nursery were not find disease that attack. The marketing area of grouper were Semarang, Jakarta, Surabaya, and local consumer.